FRI0388 ARE WE OVERLOOKING OSTEOARTHRITIS? – A COMPARATIVE STUDY OF PAIN, FUNCTION AND QUALIFY OF LIFE IN PATIENTS WITH HAND OSTEOARTHRITIS AND RHEUMATOID ARTHRITIS. (2nd June 2020) - Almeida, D.; Costa, E.; Guimarães, F.; Azevedo, S.; Rodrigues, J.; Silva, J.; Faria, D.; Teixeira, F.; Afonso, C.; Tavares-Costa, J.; Neves, J.; Ribeiro, A. R.; et al.
Abstract : Background: Osteoarthritis (OA) is frequently regarded by patients and health care providers as a normal consequence of ageing (1). On the other hand, it is well established that rheumatoid arthritis (RA) is a pathological condition requiring prompt and efficacious treatment and in which remarkable progresses have been achieved in the last decades. Pain and physical limitations are hallmarks of both conditions. Some previous studies suggest that OA and RA may have a similar burden (2, 3). Objectives: To compare levels of pain, physical disability and health-related quality of life in patients with primary hand osteoarthritis (hOA) and with RA: active disease (aRA) or in remission (rRA). Methods: Observational cross-sectional study including patients of two clinical centres with hOA and RA, either in remission or with active disease (at least two swollen and/or tender hand joints). Matching for sex and age was performed. Patients were asked to complete a survey consisting of visual analogic scale (VAS) for pain, Health Assessment Questionnaire (HAQ) and Short Form 36 (SF36). Mean values for each domain were compared between the three groups using one-way ANOVA test with significance accepted for p<.05. Results: Thirty patients with hOA and 93 with RA (33 with aRA and 60 with rRA) were included. All patients were caucasian females with no significant differences in age between groups. Patients with hOA reported higher levels of pain in comparison with aRA patients (mean VAS 57.3 vs 49.3mm, respectively, p=.265) and with rRA patients (57.3 vs 28.6mm, respectively, p<.001) [F(2.120)=25.907, p<.001]. Regarding physical function, patients with hOA reported levels of disability similar to rRA patients, but significantly lower disability than patients with aRA [F(2.120)=6.962, p=.001]. Patients with hOA evaluated their quality of life significantly better than patients with aRA and in similar levels to patients with rRA, as measured by mental health and general health status domains of SF36. Conclusion: Our results show that hOA may have similar or even higher burden of pain than RA; this is in line with previous studies, although most of them did not consider the level of inflammatory activity of RA. On the other hand, patients with hOA seem to preserve function and have better health-related quality of life despite the higher levels of pain. These results highlight OA as a cause of severe pain, which should lead us to try an optimal symptom control for these patients. These findings should also encourage rheumatologists to endeavor efforts to perform more studies in the field of OA, to better understand its pathogenesis and to eventually find disease modifying drugs. References: [1]Gignac MAM, Davis AM, Hawker G, Wright JG, Mahomed N, Fortin PR, et al. "What do you expect? You're just getting older": A comparison of perceived osteoarthritis-related and aging-related health experiences in middle- and older-age adults. Arthritis Rheum. 2006 Dec 15;55(6):905–12. [2]El-Haddad C, Castrejon I, Gibson KA, Yazici Y, Bergman MJ, Pincus T. MDHAQ/RAPID3 scores in patients with osteoarthritis are similar to or higher than in patients with rheumatoid arthritis: a cross-sectional study from current routine rheumatology care at four sites. RMD Open. 2017 Jul;3(1):e000391. [3]Slatkowsky-Christensen B, Mowinckel P, Kvien T. Health status and perception of pain: a comparative study between female patients with hand osteoarthritis and rheumatoid arthritis. Scand J Rheumatol. 2009 Jan;38(5):342–8. Disclosure of Interests: None declared